Some Volatile Aroma Components of Vitis Vinifera L. cv. Sauvignon blanc - Augustyn, 0. P. H.; Rapp, A.; van Wyk, C. J. (South African Journal of Enology and Viticulture, 2017)
Volatile aroma components of Vitis vinifera L. cv. Sauvignon blanc grapes were studied to identify the components responsible for the characteristic aroma of this grape cultivar. Thirty three volatile components were identified. Amongst these methional and trans-2, cis-6-nonadienal are reported present in Vitis for the first time. Evidence is also presented for the presence of three methoxypyrazines which are believed to be key substances responsible for the typical aroma present in grapes and wines of this cultivar.